On the Role of Bioinformatics and Data Science in Industrial Microbiome Applications - van den Bogert, Bartholomeus; Boekhorst, Jos; Pirovano, Walter; May, Ali (Frontiers in Genetics, 2019)
Advances in sequencing and computational biology have drastically increased our capability to explore the taxonomic and functional compositions of microbial communities that play crucial roles in industrial processes. Correspondingly, commercial interest has risen for applications where microbial communities make important contributions. These include food production, probiotics, cosmetics, and enzyme discovery. Other commercial applications include a software that takes the user’s gut microbiome data as one of its inputs and outputs evidence-based, automated, and personalised diet recommendations for balanced blood sugar levels. These applications pose several bioinformatic and data science challenges that range from requiring strain-level resolution in community profiles to the integration of large datasets for predictive machine learning purposes. In this perspective, we provide our insights on such challenges by touching upon several industrial areas, and briefly discuss advances and future directions of bioinformatics and data science in microbiome research.